Development of Off-Road Access Roads in Wailapia Hamlet, Larike Village, Lehitu Barat District - Buton, Idawati; Lasaiba, Mohammad Amin; Pinoa, Wiclif Sephnath (Universitas Pattimura, 2022)
This research was conducted to assess the availability of road networks in Dusun Wailapia and its impact on the mobility and activities of the community. The study identified that although road networks exist, they need to be improved, causing constraints in daily activities, especially for commuting to schools and conducting inter-village trading. The findings revealed that the existing number of transportation facilities needs to be increased to support community mobility, resulting in many still relying on private vehicles. The length of the inter-village road is approximately 1000 meters with a road width of about 3 meters, but the poor road condition hinders accessibility. The research developed several alternative strategies, including enhancing government and community collaboration, repairing and asphalting roads, and expanding public transportation facilities. The study aims to improve the quality of road networks, thereby facilitating mobility and enhancing the quality of life for the residents of Dusun Wailapia, as well as supporting economic growth and the tourism sector in the region.